Development and evaluation of passive exoskeleton (SolatExo) for assisting Muslims with physical disability in Salah - Halim, Isa; Mahadzir, Muhammad Nadzirul Izzat; Abdullah, Zulkeflee; Mohamed Sidek, Muhammad Haikal; Md Ghazaly, Mariam; Saptari, Adi (International Islamic University Malaysia (IIUM), 2025)
Performing Salah (Islamic prayer) is a fundamental practice for all Muslims worldwide, involving physical movements such as standing, bowing, and prostrating. However, these movements can be challenging for individuals with physical disabilities, who often rely on conventional chairs to support their bodies during Salah. Using conventional chairs presents limitations in mosques, disrupting congregation alignment and hindering mobility due to their bulky size and lack of portability. To address these challenges, this study aimed to design and develop SolatExo, a passive exoskeleton prototype tailored to assist Muslims with physical disabilities during Salah. The study evaluated SolatExo’s impact on range of motion (ROM), muscle contraction using electromyography (EMG), usability, and user experience. Key findings indicated no significant reduction in ROM between wearing and not wearing SolatExo. The EMG analysis revealed reduced muscle contraction with SolatExo, suggesting its potential to alleviate muscular effort during Salah. Usability assessments yielded a moderate to good System Usability Scale (SUS) score of 68, although user feedback highlighted operational difficulties, particularly during transitions between Salah postures. This study underscores the importance of interdisciplinary collaboration between biomechanics, assistive technology design, and religious studies to develop inclusive solutions for enhancing Salah accessibility. Future research should focus on refining SolatExo’s design to improve usability and user experience, addressing comfort issues and incorporating advanced ergonomics principles better to serve the diverse needs within the Muslim community.